2007
DOI: 10.4049/jimmunol.179.9.6237
|View full text |Cite
|
Sign up to set email alerts
|

The Role of IκB Kinase 2, but Not Activation of NF-κB, in the Release of CXCR3 Ligands from IFN-γ-Stimulated Human Bronchial Epithelial Cells

Abstract: The severity of chronic obstructive pulmonary disease correlates with increased numbers of cytotoxic CD8+ T lymphocytes in the lung parenchyma. CD8+ T lymphocytes release IFN-γ which stimulates airway epithelial cells to produce CXCR3 chemokines leading to further recruitment of CD8+ T lymphocytes. To evaluate the signaling pathways involved in regulation of CXCR3 ligands, the human bronchial epithelial cell line BEAS-2B was stimulated with IFN-γ and the release of the CXCR3 ligands was measured by ELISA. The … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
30
1

Year Published

2008
2008
2016
2016

Publication Types

Select...
7
2
1

Relationship

1
9

Authors

Journals

citations
Cited by 42 publications
(34 citation statements)
references
References 47 publications
3
30
1
Order By: Relevance
“…It is known that IKKb phosphorylation does not always lead to IkB degradation and NF-kB activation, and that other established IKKb cellular targets could potentially mediate the anti-adipogenic action, including IRS-1, FOXO3, and 14-3-3b (Chariot 2009). Another group has reported the same response pattern of IKKb phosphorylation without IkB degradation in human bronchial epithelial cells stimulated with interferon-g (Tudhope et al 2007). …”
Section: Discussionmentioning
confidence: 92%
“…It is known that IKKb phosphorylation does not always lead to IkB degradation and NF-kB activation, and that other established IKKb cellular targets could potentially mediate the anti-adipogenic action, including IRS-1, FOXO3, and 14-3-3b (Chariot 2009). Another group has reported the same response pattern of IKKb phosphorylation without IkB degradation in human bronchial epithelial cells stimulated with interferon-g (Tudhope et al 2007). …”
Section: Discussionmentioning
confidence: 92%
“…The chemokines act as ligands at the CXCR3 receptor, with expression peaking 8-12 h after stimulation with IFN-c [20]. This pathway is thought to be dependent on STAT1 [21]. It is worth noting that TUDHOPE et al [21] observed that this pathway was dexamethasone-resistant, a finding that is consistent with the limited impact of corticosteroids on the inflammatory profile in COPD [22].…”
Section: Genetics Of Copd Ps Bakke Et Almentioning
confidence: 87%
“…However, recent work suggests that blocking IKK activity may have widely differing results in various cell types, with its loss in activated immune cells suppressing inflammation via decreased cytokine production, and epithelial-specific ablation causing apoptosis-induced barrier disruption and initiation of mucosal inflammation (14,40,51). Additionally, as the number of IKK substrates grows, it is now clear that the IKK subunits have both pro-and anti-inflammatory functions as well as NF-B-independent targets (3,(52)(53)(54)(55). Furthermore, determining the best approach for therapeutic manipulation of this signaling pathway in intestinal disease has been hampered by the lack of tissue-specific genetic removal of NF-B subunits in the intestine.…”
Section: Discussionmentioning
confidence: 99%